AN EXPERIMENTAL STUDY ON THE EFFICACY OF VAGBHATOKTA JALA NIRVISHIKARANA YOGA ON POLLUTED WATER (International Journal of Ayurveda and Pharma Research, 2019)
Background: Increased suffering and death due to impure water consumption, along with the failure of the outreach of advanced techniques to the deprived people with middle socioeconomic status, has directed the evaluation of efficacy of the classical Ayurvedic formulations used in water purification. Aim: To evaluate the efficacy of Vagbhatokta Jala Nirvishikarana Yoga in terms of its physiochemical and antimicrobial qualities for the treatment of polluted river water.Materials and Methods: The Jala Nirvishikarana Yoga (JNY) was prepared according to the classical method, and analytical study was performed. Optimum dose and period for JNY was calculated, and the water sample was treated accordingly. The sample was analysed for various physical, chemical and microbiological parameters before and after treatment. Stability and efficacy of the formulation was determined after 3 months and 1 year. Results: JNY is a thick, alkaline and viscous liquid bearing a characteristic taste and pleasant odour. The optimum dose and period was found to be three drops per 100 mL for 30 min of contact time. No significant change in the physiochemical parameters was observed except pH. Apart from the variation in pH, JNY was observed to have antimicrobial activity. Reduction in the coliforms and inhibition of bacterial and fungal colonies in the sample were observed. JNY was observed to be stable for 1 year at room temperature. Conclusion: JNY showed efficient antimicrobial activity and was stable and effective for at least 1 year at room temperature. However, in larger doses, its administration resulted in increase of pH of water.